The palm oil export market : trends, challenges, and future strategies for sustainability - Norlin Khalid; Abdul Rahman, Nor Aida; Yan, Cheah Wai; Idris, Zainab (Routledge, 2025)
"This book provides a comprehensive examination of the palm oil export market, including analysis of its current challenges and move towards sustainability. Adopting a multidisciplinary approach, this volume is written by contributors ranging from the fields of economics, engineering, and chemical sciences. Chapters address a wide range of topics including trade market, environmental sustainability, economic dynamics, and future directions to implement nanotechnology and biowaste recycling in the palm oil industry. They synthesize existing research on the palm oil market, and examine the industry's transformation efforts via technology adoption, biofuel energy research, and its response to new rules and policies from the EU market. This book would appeal greatly to scholars and researchers on international trade, supply chain management, and economic development, especially those in oil palm production and import countries"-- Provided by publisher.
Keywords: Palm oil industry.; elektronické knihy; electronic books